Construction of Vero cell-adapted rabies vaccine strain by five amino acid substitutions in HEP-Flury strain - Harada, Michiko; Matsuu, Aya; Park, Eun-Sil; Inoue, Yusuke; Uda, Akihiko; Kaku, Yoshihiro; Okutani, Akiko; Posadas-Herrera, Guillermo; Ishijima, Keita; Inoue, Satoshi; Maeda, Ken (Scientific Reports, 2024)
Rabies virus (RABV) causes fatal neurological disease. Pre-exposure prophylaxis (PrEP) and post-exposure prophylaxis (PEP) using inactivated-virus vaccines are the most effective measures to prevent rabies. In Japan, HEP-Flury, the viral strain, used as a human rabies vaccine, has historically been propagated in primary fibroblast cells derived from chicken embryos. In the present study, to reduce the cost and labor of vaccine production, we sought to adapt the original HEP-Flury (HEP) to Vero cells. HEP was repeatedly passaged in Vero cells to generate ten- (HEP-10V) and thirty-passaged (HEP-30V) strains. Both HEP-10V and HEP-30V grew significantly better than HEP in Vero cells, with virulence and antigenicity similar to HEP. Comparison of the complete genomes with HEP revealed three non-synonymous mutations in HEP-10V and four additional non-synonymous mutations in HEP-30V. Comparison among 18 recombinant HEP strains constructed by reverse genetics and vesicular stomatitis viruses pseudotyped with RABV glycoproteins indicated that the substitution P(L115H) in the phosphoprotein and G(S15R) in the glycoprotein improved viral propagation in HEP-10V, while in HEP-30V, G(V164E), G(L183P), and G(A286V) in the glycoprotein enhanced entry into Vero cells. The obtained recombinant RABV strain, rHEP-PG4 strain, with these five substitutions, is a strong candidate for production of human rabies vaccine.